Object fixing tray for visual impairment patient - FAN MINGSI (2021)
The utility model relates to the field of medical instruments, and discloses a visual impairment patient article fixing tray which comprises a tray body, fixing belts are installed at the four corners of the tray body, hanging rings are fixedly connected to the ends, away from the tray body, of the fixing belts, and a first containing groove is formed in the rear portion of the left side of the top of the tray body. A second placement groove located in front of the first placement groove is formed in the left side of the top of the tray body, and a water cup groove is formed behind the right side of the top of the tray body. According to the article fixing tray for the visual impairment patient, the patient can take different articles according to different heights, the articles can be taken more conveniently and safely, the height and size of each functional groove are designed according to the size of the articles, the situation that the articles turn over, roll down and slip, and consequently the patient i